2013
DOI: 10.1179/2045772312y.0000000032
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling ofliver X receptor αandBcl-2-associated X proteinin experimental transection spinal cord-injured rats

Abstract: Background: Study of molecular responses to central nervous system injury would be helpful for controlling the harmful pathways post-injury and triggering the useful pathways required for the treatment of injury. Objective: To investigate the expression level of liver X receptor α (LXRα) which has anti-inflammatory effects and pro-apoptotic Bcl-2-associated X protein (Bax) upon spinal cord injury (SCI). Design: To induce SCI, transection was carried out at T9 level of male Wister rats. Approximately 8 mm of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The Bcl-2 gene family is an important regulator of apoptosis in SCI, and Bax and Bcl-2 are the most representative genes in the Bcl-2 family, which are apoptotic and anti-apoptotic genes respectively (8,9). Chen et al reported that the administration of Ad-HIF-1α ameliorates neuronal apoptosis and promotes angiogenesis through the expression of Bax/Bcl-2 in SCI rats (10).…”
Section: Introductionmentioning
confidence: 99%
“…The Bcl-2 gene family is an important regulator of apoptosis in SCI, and Bax and Bcl-2 are the most representative genes in the Bcl-2 family, which are apoptotic and anti-apoptotic genes respectively (8,9). Chen et al reported that the administration of Ad-HIF-1α ameliorates neuronal apoptosis and promotes angiogenesis through the expression of Bax/Bcl-2 in SCI rats (10).…”
Section: Introductionmentioning
confidence: 99%
“…Both Bax and Bcl-2 are quintessential genes in Bcl-2 family, with Bax being the apoptotic gene and Bcl-2 being the antiapoptotic gene. The ratio of Bcl-2 to Bax is considered a decisive factor and plays an important role in determining whether cells will undergo apoptosis (Luo et al, 2015;Mohammadi, Ghaedi, Esmailie, & Rahgozar, 2013). Whereas positive intensity of both Bax and caspase-3 were abruptly increased on day 14 in the anterior horn of injured spinal cord, Bcl-2 intensity was gradually decreased between days FIGURE 7 Ultra-structural examinations, as described under the materials and method section, showed morphological changes in myelin sheath and axons.…”
Section: Discussionmentioning
confidence: 99%
“…Both Bax and Bcl‐2 are quintessential genes in the Bcl‐2 family and represent apoptotic as well as anti‐apoptotic genes, respectively. The ratio of Bcl‐2 to Bax is considered a decisive factor and plays an important role in determining whether or not cells will undergo apoptosis (Mohammadi et al, ; Luo et al, ). Our results indicated that Bax positive cells gradually abated and was subsequently chaperoned by the upregulation of intensity in the anterior horn of the spinal cord in both Cur‐ and MP‐treated groups.…”
Section: Discussionmentioning
confidence: 99%